1976
DOI: 10.1073/pnas.73.4.1149
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic stability of helical RNA: a selective advantage for the natural 3',5'-bond.

Abstract: Dodecaadenylic acid containing a single 2',5'-linkage at a defined position was formed by the coupling of two hexamers on a poly(U) template at 20. The rate of hydrolysis of this dodecamer was compared with that of a dodecamer that contained only the natural 3'-'-linkages. At 400, in 1 M aqueous ethylenediamine at pH 8 in the absence of poly(U), both dodecamers hydrolyzed at comparable rates, but the addition of two equivalents of poly(U) caused a 7-fold increase in the initial rate of hydrolysis of the oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
104
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(111 citation statements)
references
References 25 publications
6
104
0
1
Order By: Relevance
“…In particular, 2 ,3 cyclic phosphate bridges were reported to promote the formation of phosphodiester bonds connecting preformed oligonucleotides bound to the appropriate sequence-complementary strands in the absence of catalysts [108]. In this system, in addition to the capacity to form phosphate bridges, the higher stability of 3 ,5 bonds relative to 2 ,3 bonds in double-stranded RNA structures was observed [109]. In the presence of 1-2 diamino ethane at alkaline pH the self-polymerization of 2 ,3 cyclic adenosine mono-phosphate (2 ,5 cAMP) was described [110].…”
Section: Abiotic Rnamentioning
confidence: 91%
“…In particular, 2 ,3 cyclic phosphate bridges were reported to promote the formation of phosphodiester bonds connecting preformed oligonucleotides bound to the appropriate sequence-complementary strands in the absence of catalysts [108]. In this system, in addition to the capacity to form phosphate bridges, the higher stability of 3 ,5 bonds relative to 2 ,3 bonds in double-stranded RNA structures was observed [109]. In the presence of 1-2 diamino ethane at alkaline pH the self-polymerization of 2 ,3 cyclic adenosine mono-phosphate (2 ,5 cAMP) was described [110].…”
Section: Abiotic Rnamentioning
confidence: 91%
“…The 2′-5′ linkage is an alternative form of nucleic acid backbone in addition to the 3′-5′ linkage during molecular evolution (42,43). Previous studies have demonstrated that a mixture of 2′-5′ and 3′-5′ phosphodiester linkage can be obtained during nonenzymatic RNA replication, suggesting a high probability of mixture of phosphodiester linkages in the early evolution of life (3)(4)(5)(6)(7)(8)(9). It is conceivable that RNA in early evolution of life may have contained a mixture of 2′-5′ and 3′-5′ phosphodiester linkages.…”
Section: Insights Into Molecular Evolution Of Phosphodiester Linkagementioning
confidence: 99%
“…Indeed, previous studies revealed that nonenzymatic RNA replication would lead to a mixture of 2′-5′ and 3′-5′ linkages (Fig. 1A) (3)(4)(5)(6)(7)(8)(9). The 2′-5′-linked nucleic acids can form duplex structures by themselves or by pairing with natural nucleic acids (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 96%
“…Nevertheless, the question of how RNA might have evolved to the exclusively 3′,5′‐linked material that is primarily employed by extant biology remains largely unanswered. The well‐known preferential hydrolysis of 2′,5′‐bonds in a helical context11, 13 might have played a key role in this transition, with 3′,5′‐linkages becoming enriched simply through the depletion of 2′,5′‐linked material. However, rather than just degrading RNA, a more plausible scenario would embrace recycling, with formation of new 3′,5′‐bonds through repair of the broken linkages.…”
mentioning
confidence: 99%
“…Under these conditions, both the intact oligomers and the produced fragments are expected to be mainly helical (as estimated by melting point measurements; Figure S2), thereby preventing any degradation of single‐stranded RNA 13. The HPLC was performed under denaturing conditions, however, to allow separation and quantitation of the various species.…”
mentioning
confidence: 99%